PI3K/AKT/mTOR pathway inhibitors in triple-negative breast cancer: a review on drug discovery and future challenges. Issue 11 (November 2019) - Khan, Mohammad A.; Jain, Vineet K.; Rizwanullah, Md.; Ahmad, Javed; Jain, Keerti
Highlights: TNBC represents the most aggressive phenotype of breast cancer. Conventional therapy prescribed for breast cancer is not effective in treatment of TNBC. Specific therapeutic targets must be identified in TNBC. The PI3K/Akt/Mtor (PAM) pathway is an important signaling pathway of TNBC. Drug molecules targeting the PAM pathway could emerge as promising therapeutics. Abstract : Triple-negative breast cancer (TNBC) is a highly malignant subtype of breast cancer associated with poor prognosis. Although conventional chemotherapy regimens have shown some effectiveness in early TNBC cases, the outcome in advanced stages is poor. The PI3K/AKT/mTOR pathway is one of the important and active pathways involved in chemoresistance and survival of TNBC. This pathway is speculated to play an important part in malignant transformation and has been considered as a potential molecular target for the design of therapeutic agents to treat TNBC. This review discusses the potentials and drug discovery perspectives of PI3K/AKT/mTOR as a therapeutic target for effective management of TNBC with anticipated challenges.